1999
DOI: 10.1016/s0008-6363(98)00335-6
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin inhibition and atrial natriuretic peptide release after acute volume expansion in rats with aortocaval shunt

Abstract: Our data suggest that the ANP system is impaired in rats with aortocaval shunt. The activation of the angiotensin system contributes to the impairment of the ANP system. Acute inhibition of the angiotensin II system significantly improved the ability of the ANP system to respond to acute volume expansion. Our findings indicate a hitherto fore unappreciated interaction between both systems and suggest additional mechanisms for the beneficial effects of angiotensin converting enzyme inhibition or angiotensin II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Langenickel et al (16) showed that ANP mRNA was upregulated in the LA of shunted rats, whereas the RA ANP mRNA expression remained unchanged. Willenbrock et al (25) found unchanged ANP mRNA as well as ANP concentration in both the LA and RA in this heart failure model. These data suggest that the blunted ANP release we observed in shunt animals was neither due to impaired synthesis nor depleted storage vesicles of ANP.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…Langenickel et al (16) showed that ANP mRNA was upregulated in the LA of shunted rats, whereas the RA ANP mRNA expression remained unchanged. Willenbrock et al (25) found unchanged ANP mRNA as well as ANP concentration in both the LA and RA in this heart failure model. These data suggest that the blunted ANP release we observed in shunt animals was neither due to impaired synthesis nor depleted storage vesicles of ANP.…”
Section: Discussionmentioning
confidence: 46%
“…In several models of experimental heart failure as well as in human heart failure, ANP release after either acute volume load or exercise is blunted (7,13,17,18,24,25). Willenbrock et al (25) suggested that the ANP system is impaired in rats with an acute aortocaval shunt and that the activation of the angiotensin system contributes to the impairment of the ANP system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The renin-angiotensin-aldosterone system (RAAS) is activated in rats with aortocaval fistula as evidenced by an increased plasma concentration of angiotensin II (Ang II) and, in rats with a large fistula, an increased plasma renin activity (Ruzicka et al 1993;Willenbrock et al 1999). Furthermore, cardiac angiotensin-converting enzyme (ACE) 1 expression is upregulated, whereas that of ACE2 is reduced, indicating that the local cardiac RAAS is also activated (Karram et al 2005).…”
Section: Introductionmentioning
confidence: 99%